Architecting Cloud Computing Solutions - Scott Goessling; Kevin L. Jackson (Packt Publishing, 2018)
In "Architecting Cloud Computing Solutions," you will explore foundational concepts and practices for effectively designing and implementing cloud computing infrastructures. From understanding different deployment and service models to leveraging advanced tools like Cloud-Native and serverless architectures, this book equips you to build scalable, secure, and cost-efficient cloud environments tailored to your organization's needs.What this Book will help me doManage changes effectively during your organization's transition to the cloud.Gain expertise in designing architectures that address specific business needs.Learn baseline cloud architecture modification and aggregation techniques.Understand security implications in cloud applications and mitigate related threats.Architect small to large-scale cloud solutions suitable for enterprises or startups.Author(s)Kevin L. Jackson is an accomplished cloud computing expert with years of hands-on experience in IT infrastructure. Together with None Goessling, they offer a practical approach to cloud solution architecture, blending strategic insights with technical depth, ensuring that readers gain real-world capabilities to address modern business IT challenges.Who is it for?This book is ideal for IT administrators, cloud architects, and solution architects eager to leverage the benefits of cloud computing. It's also suitable for small business managers or consultants exploring cloud solutions for scalability and efficiency. Even if cloud computing is entirely new to you, this text provides an accessible starting point to skillfully navigate this field.